O problema da violência escolar: uma clarificação e diferenciação de vários conceitos relacionados - Maria José D. Martins (Revista Portuguesa de Educação, 2005)
In this article we review the literature and reflect about the theme of school violence, and also about all the concepts that are related with that theme, namely: indiscipline, anti-social conduct, delinquency, conduct disorder and bullying. We clarify and differentiate these concepts in view of their operational definition and relation in future investigations.